Monitoring progress in multi-dimensional poverty reduction: A person-focused and inequality-sensitive approach with evidence from Nicaragua - José Espinoza-Delgado (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2020)
In this paper, considering the overarching concern of the 2030 sustainable development agenda, "leaving no one behind", and targets 1.2 and 10.1 of the SDGs, we stress that the mainstream approach to multidimensional poverty measurement in developing countries faces some deficiencies to properly monitor progress in multidimensional poverty reduction, mainly because it uses the household as the unit of identification, ignoring thus intra-household inequalities, and is totally insensitive to inequality among the multi-dimensionally poor individuals, a serious defect of any poverty measure. Consequently, we propose to depart somewhat from the mainstream approach and to adopt a person-focused and inequality-sensitive framework, which is applied to the case of Nicaragua. Overall, we find that in this country, multidimensional poverty decreased between 2001 and 2014, but inequality among the multi-dimensionally poor individuals, an issue that has been ignored by the mainstream approach, increased substantially during that period; in other words, people's deprivation scores were less unequally distributed in 2001 than in 2014. These findings suggest that progress in multidimensional poverty reduction in Nicaragua seems to be leaving behind the poorest of the poor, challenging thus the overarching concern of the SDGs agenda.
Keywords: I3; I32; D1; D13; D6; D63; O5; O54; 330; multi-dimensional poverty; individual-based measures; inequality-sensitive measures; Nicaragua; Latin America and the Caribbean